Exploring the outcomes of psychotherapy sessions: how do therapists' responsiveness and emotional responses to patients with personality disorders affect the depth of elaboration? - Fiorentino, Flavia; Gualco, Ivan; Carcione, Antonino; Lingiardi, Vittorio; Tanzilli, Annalisa (Frontiers in Psychology, 2024)
The impact of depth of elaboration in individual psychotherapy sessions on overall treatment effectiveness was found in the empirical literature. In the best sessions, relevant content is processed with greater depth; in contrast, in the shallower sessions, the emerging content is more superficial. Evidence suggests that achieving a high level of depth is closely related to specific therapist characteristics and relational dimensions (including clinicians' emotional responses to patients). The present study aimed to (a) compare therapist responsiveness and countertransference patterns in psychotherapy sessions with different levels of depth of elaboration; and (b) examine if the positive countertransference pattern mediated the relationship between therapist responsiveness and depth of elaboration. Eighty-four clinicians were asked to select one patient with personality disorders in their care and complete the Depth Scale of the Session Evaluation Questionnaire, the Patient's Experience of Attunement and Responsiveness Scale, and the Therapist Response Questionnaire concerning one of their sessions. The results showed that sessions with higher levels of depth of elaboration were characterized by greater therapist responsiveness and more positive countertransference. Conversely, poor therapist responsiveness and hostile/angry, disengaged, and helpless/inadequate countertransference responses were found in shallower sessions. Moreover, positive countertransference mediated the relationship between therapist responsiveness and depth of elaboration. This study sought to shed light on the processes underlying the outcomes of psychotherapeutic sessions, highlighting the strong impact of relational factors. Advancing knowledge of these mechanisms seems crucial to identifying the active ingredients of the therapeutic process and understanding what (does not) promote successful outcomes.